Occurrence characteristics and transport processes of riverine microplastics in different connectivity contexts - Feiyang Xia; Wei Yang; Haixiao Zhao; Yanpeng Cai; Qian Tan (npj Clean Water)
Abstract This study is the first to quantify the migration processes of riverine microplastics under different connectivity contexts based on the spatial variation characteristics of microplastic loads. Microplastics in multidammed, single-dammed, and nondammed rivers are significantly different in three categories: abundance, flux, and inventory. Artificial damming can lead to multicategory reorganization of riverine microplastics, including size, polymer type, shape, and color. Artificial damming has led to the formation of microplastic hotspots in river waters and sediments due to reduced river mobility. Notably, low-velocity regions in non-dammed rivers are high hotspot for microplastic deposition, and their inventories may even be 10.63–12.71 times higher than those of other riverbeds. Additionally, results based on microplastic abundance differ significantly from those based on microplastic loads, which in some cases even showed contradictory results. Therefore, future studies must incorporate microplastic loads into the assessment to enhance our understanding of the fate of microplastics in river systems.